The Effect of Brand Experience, Brand Satisfaction, Brand Trust and Brand Loyalty Users of Janji Jiwa Coffee Application (Jiwa+) - Raprini Meidina; Rusdi Musa Ishak; Miguna Astuti (Garuda Prestasi Nusantara Consulting, 2022)
This study is to analyze brand loyalty among users of the Janji Jiwa Coffee (Jiwa+) application in Jakarta. This study aims to determine the effect of Brand Experience, Brand Satisfaction, Brand Trust and Brand Loyalty. During the covid 19 pandemic, Janji Jiwa Coffee presents the Jiwa+ application to make it easier for consumers to place orders by utilizing GPS technology to refer the nearest outlet to their consumers. Descriptive and inferential approaches are used in this study. Researchers used quantitative data in the form of primary data. The sample in this study amounted to 106 people who are Janji Jiwa Coffee consumers who use the application (Jiwa+). Collecting data using e-questionnaire (google form). Data analysis technique is processed using Partial Least Square (PLS). The results for brand experience and brand satisfaction has an effect on brand loyalty, while for brand trust has no effect on brand loyalty. Then brand experience, brand satisfaction affects brand trust and brand experience affects brand satisfaction. Keywords: Brand Experience, Brand Satisfaction, Brand Trust and Brand Loyalty